Mechanical complications after central venous catheterisation in the ultrasound-guided era: a prospective multicentre cohort study. (December 2022) - Adrian, Maria; Borgquist, Ola; Kröger, Tina; Linné, Erik; Bentzer, Peter; Spångfors, Martin; Åkeson, Jonas; Holmström, Anders; Linnér, Rikard; Kander, Thomas
Abstract: Background: Limited data are available on the incidence of mechanical complications after ultrasound-guided central venous catheterisation. We aimed to determine the incidence of mechanical complications in hospitals where real-time ultrasound guidance is clinical practice for central venous access and to identify variables associated with mechanical complications. Methods: All central venous catheter insertions in patients ≥16 yr at four emergency care hospitals in Sweden from March 2, 2019 to December 31, 2020 were eligible for inclusion. Every insertion was monitored for complete documentation and occurrence of mechanical complications within 24 h after catheterisation. Multivariable logistic regression analyses were used to determine associations between predefined variables and mechanical complications. Results: In total, 12 667 catheter insertions in 8586 patients were included. The incidence (95% confidence interval [CI]) of mechanical complications was 7.7% (7.3–8.2%), of which 0.4% (0.3–0.5%) were major complications. The multivariable analyses showed that patient BMI <20 kg m −2 (odds ratio 2.69 [95% CI: 1.17–5.62]), male operator gender (3.33 [1.60–7.38]), limited operator experience (3.11 [1.64–5.77]), and increasing number of skin punctures (2.18 [1.59–2.88]) were associated with major mechanical complication. Subclavian vein catheterisation was associated with pneumothorax (5.91 [2.13–17.26]). Conclusions: The incidence of major mechanical complications is low in hospitals where real-time ultrasound guidance is the standard of care for central venous access. Several variables independently associated with mechanical complications can be used for risk stratification before catheterisation procedures, which might further reduce complication rates. Clinical trial registration: NCT03782324.